Sosialisasi Di Sekolah Se-Kota Serang Wajah Baru Seragam Sekolah Di Indonesia Sebagai Pemantik Semangat Belajar Dalam Upaya Menciptakan Nuansa Baru Dunia Pendidikan - ELI APUD SAEPUDIN; Dede Qodrat Al Wajir; Parko Prahima; Arief Rachman; Marini Magdalena (Yayasan Perguruan Kampus, 2024)
Appearance can have a significant impact on a person's life. An attractive appearance can boost confidence, impress others and open up new opportunities. However, appearance can also be a source of discrimination and prejudice. It is important to remember that appearance is only one aspect of a person. Appearance should not be the only factor used to judge a person. The method of implementing socialization with the zoom method to schools in the city of Serang, the results obtained are where students and female students have high confidence in Teaching and Learning Activities KBM is based on the Regulation of the Minister of Education and Culture Number 50 of 2022 where elementary, junior high, high school students have the main objectives Increasing uniformity and national identity of students, Eliminating discrimination based on economic status, Freeing students from pressure to follow fashion trends and Focusing attention on education.